Identification of in vivo-expressed antigens of Staphylococcus aureus and their use in vaccinations for protection against nasal carriage. - Clarke, SR; Brummell, K; Horsburgh, M; McDowell, P; Mohamad, SA; Stapleton, MR; Acevedo, J; Read, R; Day, N; Peacock, S; Mond, J; Kokai-Kun, J; et al. (2006)
A spectrum of in vivo-expressed Staphylococcus aureus antigens was identified by probing bacteriophage expression libraries of S. aureus with serum samples from infected and uninfected individuals. Eleven recombinant antigenic proteins were produced, and specific antibody titers in a large collection of human serum samples were determined. Significantly increased concentrations of reactive immunoglobulin G (IgG) to 7 antigens were found in serum samples from ill individuals, compared with those in healthy individuals. Significantly higher concentrations of reactive IgG to 4 antigens, including iron-responsive surface determinant (Isd) A and IsdH, were found in serum samples from healthy individuals who were not nasal carriers of S. aureus, compared with those in healthy carriers. Vaccination of cotton rats with IsdA or IsdH protected against nasal carriage. Also, IsdA is involved in adherence of S. aureus to human desquamated nasal epithelial cells and is required for nasal colonization in the cotton rat model. Thus, vaccination with these antigens may prevent S. aureus carriage and reduce the prevalence of human disease.